Risk factors and prognostic impact of post-discharge bleeding after endovascular therapy for peripheral artery disease. (June 2021) - Hishikari, Keiichi; Hikita, Hiroyuki; Abe, Fumichika; Ito, Naruhiko; Kanno, Yoshinori; Iiya, Munehiro; Murai, Tadashi; Takahashi, Atsushi; Yonetsu, Taishi; Sasano, Tetsuo
This study evaluated the incidence, predictors, and impact of bleeding requiring hospitalization following successful endovascular therapy (EVT) for peripheral artery disease. Platelet inhibition after EVT reduces the risk of major adverse limb events but increases the risk of bleeding. The incidence of post-discharge bleeding after EVT, its independent predictors, and its prognostic importance in clinical practice have not been fully addressed. We evaluated 779 consecutive patients who underwent EVT. We found that 77 patients (9.9%) were hospitalized for major bleeding during follow-up after EVT (median 39 months, range 22–66 months), with almost half (48.1%) of the bleeding categorized as gastrointestinal bleeding. Significant predictors of post-discharge bleeding were hemodialysis (hazard ratio (HR), 3.12; 95% CI: 1.93 to 5.05; p < 0.001) and dual antiplatelet therapy (DAPT) use (HR, 1.87; 95% CI: 1.03 to 3.41; p = 0.041). During follow-up, the all-cause mortality-free survival rate was significantly worse in patients who had experienced major bleeding than in those who had not (log-rank test χ 2 = 54.6; p < 0.001). Cox proportional hazards analysis showed that major bleeding (HR, 2.78; 95% CI: 1.90 to 4.06; p < 0.001) was an independent predictor of all-cause death after EVT. Hospitalization for post-discharge bleeding after EVT is associated with a substantially increased risk of death, even after successful EVT. We concluded that patients' predicted bleeding risk should be considered when selecting patients likely to benefit from EVT, and that the risk should be considered especially thoroughly in hemodialysis patients.